Mycoses associated with AIDS in the Third World - Marques, Silvio Alencar [UNESP]; Robles, A. M.; Tortorano, A. M.; Tuculet, M. A.; Negroni, R.; Mendes, Rinaldo Poncio [UNESP] (B I O S Scientific Publishers Ltd, 2000)
Despite advances in diagnosis and treatment, the epidemiological status of the human immunodeficiency virus (HIV) infection is far from under control in most of the developing world. Sub-Saharan Africa, Southeast Asia and India show increased rates of new infections. In Latin America and the Caribbean there were 1.6 million estimated cases of HIV-infected patients at the end of 1997. Fungal diseases have been one of the most relevant diagnoses in relation to the acquired immunodeficiency syndrome (AIDS), Infections due to Candida species and Cryptococcus neoformans var, neoformans are common worldwide. Histoplasma capsulatum, Coccidioides immitis and Penicillium marneffei are important causes of disease in endemic areas. Infection due to Sporothrix schenckii, Blastomyces dermatitidis and Paracoccidioides brasiliensis are uncommon even where they are endemic. Phaeohyphomycetes, hyalohyphomycetes and zygomycetes are still rare as a cause of disease among AIDS patients, However, agents pertaining to these groups, such as Aspergillus spp., have an increasing incidence. Superficial mycoses due to dermatophytes have special features from epidemiological, clinical and therapeutic points of view.
Keywords: fungal infections in AIDS; mycosis in Third World; systemic fungi